Development of Learning Tools Based on the Think Pair Share Model to Improve Fourth-Grade Students' Cooperation Skills - Aisyah Sakinah Akbar (Sains Global Institut, Indonesia, 2026)
This study aims to develop learning tools based on the Think Pair Share model on the topic of cooperation for fourth-grade elementary school students. This study employs the Research and Development (R&D) method using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. However, this study is limited to the development and theoretical evaluation stages through a literature review approach without direct field testing. The background of this study is based on observations conducted at SD Negeri Tidung, which revealed that learning activities still tend to use conventional methods, making learning less engaging and unable to optimally improve students' cooperation skills. The analysis stage involved identifying students' needs and characteristics. The design stage included designing learning tools based on the Think Pair Share model, while the development stage focused on creating interactive learning tool products. Evaluation was conducted based on literature reviews and relevant previous studies. The findings indicate that learning tools based on the cooperative learning model Think Pair Share have the potential to improve motivation, engagement, and cooperation skills among fourth-grade elementary school students. Therefore, the developed learning tools are considered theoretically feasible as an innovative learning alternative that aligns with the characteristics of fourth-grade elementary school students.